General Trends in Art Education Development in the Territory of Ukraine As Part of the Russian Empire in the Second Half of the 19th and Early 20th Centuries - Boichenko, Maryna; Nykyforov, Andrii; Hulei, Olha (Journal of History Culture and Art Research, 2020)
The article aims to determine the main stages of teaching fine, decorative, and applied arts in the context of art education development in Ukraine, which in the second half of the 19th – early 20th centuries was part of the Russian Empire. The methodology of the study consists of a set of methods of analysis, synthesis, comparison, generalization, interdisciplinary synthesis of historical-cultural, historical-artistic, and historical-pedagogical approaches. The scientific novelty lies in generalizing comprehension of art education progressive development in Ukraine in the 19th – early 20th centuries, expanding theoretical ideas about peculiarities of the stages of teaching fine, decorative, and applied arts in the territory that was part of the Russian Empire. The study of the main trends – changes in social conditionality, requests of society for skilled handicraft and pedagogical staff of artistic and crafts profile, processes of art education formation and development of cultural-artistic trends in the field of fine, decorative, and applied arts, using a number of socio-economic, educational, cultural-artistic criteria, allowed to distinguish the stages of the process of organizing the teaching of art disciplines in the specified region of the second half of the 19th – early 20th century. At the same time, the forms of connections and mutual influences formed in the course of a general historical-pedagogical process between vocational and art-crafts education and in the unity of cultural-educational and educational-artistic processes reflected in the normative-legal base of national art education development were taken into account. Analysis of research results gives an opportunity to understand the trends in national art education development in Ukraine as part of the Russian Empire in connection with the current social processes.